Proximate and organoleptic analysis of plantain-based snack (plantain mosa) and puff-puf (2024)
Ready to eat dry foods refrigerated meals, shelf stable food etc mixes like cake mixes are all examples of convenience foods in Nigeria. Organoleptic properties of food such as color, taste, flavor, aroma, and texture have distinct and influential effect on food acceptability and specifically influence the decision that a consumer makes regarding the preference of food substance. Despite being a rich source of complex carbs vitamins and minerals, plantains are quite simple to digest. It serves only as a replacement side dish and is often consumed with other foods. It has not yet been completely developed to create snack items in terms of vitamins and other nutrients. This study aimed at investigating the proximate and organoleptic analysis of plantain mosa and puff-puff and specifically compared the level of their acceptability. Proximate analysis of plantain mosa and puff-puff were carried out in the Laboratory to ascertain their level of composition of moisture content, protein, fat, ash, crude fibre and carbohydrate. One hundred samples of sensory evaluation forms were administered to respondents comprising of all kind of visitors at University of Ibadan Hotel under University of Ibadan ventures in its environ to assess the organoleptic properties of plantain mosa and puff-puff to determine most preferred sample. Random and convenience sampling were used to determine the respondents at the hotel. Data were analyzed using descriptive statistics (use of charts and percentage). The findings included variations in the proximate analysis value of Plantain mosa and puff-puff.